Covenant design in financial contracts: a case study of the private equity acquisition of HCA - Wei, Tzu-Wen; Lee, Jyh-An; Huang, Chi-Jui; Dong, Tse-Ping (International Journal of Strategic Property Management, 2015)
A buyout deal involves several parties, including private equity firms, the target company, and lending banks. All these parties are legally connected by contractual arrangements, and covenants among all interest parties are important. However, a comprehensive study on designing covenants among parties in a buyout deal to achieve commitment and avoid risk in closing a deal is seldom seen in current literature. By investigating one of the world's largest buyout deals – the acquisition of Hospital Corporation of America (HCA), this paper not only probes into the design of contracts and covenant, but also provides several managerial implications. This paper concludes that well-designed covenants in buy-out deals can appropriately align all participants’ diversified interests.First Publish Online: 23 Dec 2015